Characterization of Amino-Functionalized Ferromagnetic Nanoparticles with Glutaraldehyde Cross-linking - Sukprasert, Jaravee; Thumanu , Kanjana; Phung-on, Isaratat; Jirarungsatean, Chalermkiat; Chaisalee, Peerapon; Tuitemwong, Pravate; Tuitemwong, Kooranee (Journal of Science and Technology, 2021)
Characterization of amino-functionalised magnetic nanoparticles (FMNs) modified surfaces with glutaraldehyde cross linker, which enables the attachment to a specific antibody against Salmonella was examined using FTIR spectroscopy. The magnetism property of the particles before and after attachment to the target cells was studied. Synchrotron FTIR spectroscopy technique was employed to investigate the chemistry of the crosslinking reaction to amino-functionalized ferromagnetic nanoparticles. Results indicated that the bonding pattern imine bond (C=N) and amide bond (-CONH-) were detected. The finding indicated the attachment of aldehyde group (CHO) to amino region of the particle and the other free end to link to the antibodies against Salmonella. The bonding allowed the antibodies to bear reactive sites to catch the target Salmonella in food samples. The FMNs demonstrated hysteresis characteristics that could be changed due to cell attachment that caused reduction of loop coercive force (H). Results showed evidence of glutaraldehyde crosslinking that could be also used as quality control for immobilization of antibodies to the particles. Magnetism properties (the coercive force H) and FTIR characteristics could be further used for signal of attachment of cells to the FMNs as well.